Perlindungan Hukum Terhadap Anak Dibawah Umur yang Menjadi Korban Tindak Pidana Pencabulan - Aji Titin Roswitha Nursanthy; Gunawan Hasibuan; Ni Kadek Dewi Ayu Lestarie (LPPM STIH Awang Long, 2021)
Child molestation is a crime that violates morals, ethics and religion. The impact of this crime on children is that it causes physical and psychological trauma to victims, especially those who are children so that it can affect the victim's self-development when he grows up. The results of the research and discussion show: Factors that can increase and influence the occurrence of criminal acts of sexual abuse against minors, namely: low education and economic factors, environmental or residential factors, drinking factors (alcohol), technological factors and victim role factors in the realm of criminological etiology can be categorized in the theory that is not oriented to social class. Efforts to tackle the crime of sexual abuse of minors can be done in two ways, namely prevention and mitigation if the crime of sexual abuse of minors has already occurred. In the context of protection for victims of crime, there are preventive and repressive measures taken, both by the community and the government (through law enforcement officers), such as providing protection/supervision from various threats that can endanger the lives of victims, providing adequate medical and legal assistance, A fair examination and judicial process against perpetrators of crimes is basically one of the manifestations and protections of human rights as well as a balancing instrument. This is where the philosophical basis behind the importance of crime victims (their families) gain protection.